The Good, the Bad, and the Ugly of Data Migration: a Case Study with ECU - Thomas, William Joseph; Zhou, Ying; Fey, Melba; Rosen, Andrew (My University, 2018)
In 2016, East Carolina University sought a user-friendly, innovative system for faculty activity reporting to replace their current technology. Although their requirements were straightforward—integration with institutional data and external bibliographic sources, flexible reporting functions, and faculty networking capabilities—the challenges of implementation demanded an organized, institutional-wide effort as well a strategic transition plan with their new partner, Interfolio. This presentation focuses on the good (capabilities gained from Interfolio’s robust, faculty-focused reporting platform), the bad (the pain of migrating legacy data), and the ugly (unexpected complications) of data integration so that other IR leaders can plan when implementing similar systems on their campus.